Redescription of apolonia tigipioensis torres and braga, 1938 (Trombidiformes: Leeuwenhoekiidae) - Bassini-Silva, Ricardo; Jacinavicius, Fernando C.; Welbourn, Warren C.; Ochoa, Ronald; Barros-Battesti, Darci M. [UNESP] (Tyumen State University, 2018)
The genus Apolonia is only known from the single species, Apolonia tigipioensis Torres et Braga, occurring in Venezuela and northeastern Brazil. The larval stage is primarily a parasite of birds, but they may parasitize mammals, including humans. This species can cause nodular lesions in birds. In the present study, we are redescribing the species A. tigipioensis based on the slides deposited at the Acari Collection of the Butantan Institute. Furthermore, we designate a lectotype and paralectotype for this species.
Keywords: Birds; Brazil; Chiggers; Ectoparasites